2009
DOI: 10.1093/ndt/gfp517
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinical dry weight assessment in haemodialysis patients using bioimpedance spectroscopy: a cross-sectional study

Abstract: BIS is an interesting, objective method to support clinical DWA. Further studies should be performed to investigate beneficial clinical effects of this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
131
2
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(142 citation statements)
references
References 12 publications
2
131
2
7
Order By: Relevance
“…The complementary prognostic information provided by these simple investigations is of major importance for identifying subpopulations that may benefit from a specific intervention and for the design of future randomized trials in patients with chronic kidney disease. Recent studies have demonstrated that brachial pulse pressure, a proxy of arterial stiffness, is an important parameter to take into account when deciding on fluid removal and dry weight (8,9). For the management of hyperphosphatemia, the choice of phosphate binder (calcium-versus noncalcium-containing) may be influenced by the degree of vascular calcification, if the available data on the adverse effect of calcium salts on the progression of vascular calcification and outcome are confirmed (10 -12).…”
Section: Discussionmentioning
confidence: 99%
“…The complementary prognostic information provided by these simple investigations is of major importance for identifying subpopulations that may benefit from a specific intervention and for the design of future randomized trials in patients with chronic kidney disease. Recent studies have demonstrated that brachial pulse pressure, a proxy of arterial stiffness, is an important parameter to take into account when deciding on fluid removal and dry weight (8,9). For the management of hyperphosphatemia, the choice of phosphate binder (calcium-versus noncalcium-containing) may be influenced by the degree of vascular calcification, if the available data on the adverse effect of calcium salts on the progression of vascular calcification and outcome are confirmed (10 -12).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, fluid and salt restrictions are the principle means used to minimize IDWG and thereby, rapid UF rates, but research and clinical experience show that adherence to these otherwise physiologically sound interventions is difficult (7,8). As a result, as many as 25%-50% of patients on HD are chronically volume-expanded, and many patients are routinely exposed to high UF rates (9). To mitigate risk from hypervolemia and fluid removal practices, novel approaches to fluid management are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Bioimpedance spectroscopy represents a different approach to the assessment of fluid status and this analytic technique mainly uses the electrical properties of biological cells and fluids (33)(34)(35). The Body Composition Monitor is a bioimpedance spectroscopy device for clinical use, validated by isotope dilution methods (6), and reference body composition methods (7), and has been used in hemodialysis patients (21,(36)(37)(38). Moving patients into the normohydration target range leads to a better control of hypertension (38,39), fewer intradialytic adverse events and improved cardiac function (38,40).…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Nementioning
confidence: 99%